Radiation Curing of Thermosetting-Thermoplastic Blends as Matrices for Structural Carbon Fibre Composites - Alessi, Sabina; Dispenza, Clelia; Pitarresi, Giuseppe; Spadaro, Giuseppe (IntechOpen, 2011)
None